Gambaran Pemakaian Bahan Medis Habis Pakai Gudang Depo Farmasi Rindu B RSUP H. Adam Malik Medan Berdasarkan Standar Operasional Prosedur Tahun 2019 - Anjur Falden Lingga; Adek Chan; Suprianto (Jurnal Indah Sains dan Klinis, 2023)
Introduction: Managing consumable medical materials involves coordinating activities to ensure they work well together, aiming for effective and efficient management. This ensures doctors always have an adequate supply of high-quality consumable medical materials to support quality services. Objective: This study aimed to describe the Utilization of Consumable Medical Materials at the Pharmacy Warehouse of Depo Rindu B H. Based on the 2019 Standard Operating Procedures (SOP), Adam Malik Hospital Medan. Methods: The study utilized direct observation and interviews conducted from May to July 2019. Results: Expenditures in January, February, and March 2019 were 25,726, 22,332, and 24,503 units respectively. Distribution is facilitated through online prescribing and delivery. Observations indicated the use of storage systems such as First In First Out (FIFO) and First Expired First Out (FEFO), organised by dosage form, alphabetical order, and category. Conclusion: Procurement at the Depo Rindu B pharmaceutical warehouse at H. Adam Malik Hospital Medan during the 2019 period was by the applicable 2019 SOP